1993
DOI: 10.1128/iai.61.3.1105-1112.1993
|View full text |Cite
|
Sign up to set email alerts
|

Induction of murine T-helper-cell responses to the filarial nematode Brugia malayi

Abstract: The purpose of this study was to examine the murine T-helper-cell (Th) cytokine response to the human filarial parasite Brugia malayi. In the first 14 days following intraperitoneal inoculation of live microfilariae into BALB/c mice, filarial antigen-driven splenic lymphoid cells produced gamma interferon (IFN-y) and little or no interleukin-5 (IL-5). After this time, IL-5 production increased (to 10 to 12 ng per 5 x 106 cells) coincident with a marked diminution in IFN-y generation. A single subcutaneous immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 25 publications
(18 reference statements)
2
40
1
1
Order By: Relevance
“…Although this response could be modulated by IL-12, there was no effect on clearance of blood microfilaremia after i.v. injection (Pearlman et al 1995a). The current study demonstrates that IL-12 significantly down-modulates the physiological and immunological changes in the lung that are induced by B. malayi larvae, including airway eosinophilia, deposition of eosinophil granule proteins and tracheal hyperreactivity.…”
Section: Discussionmentioning
confidence: 54%
“…Although this response could be modulated by IL-12, there was no effect on clearance of blood microfilaremia after i.v. injection (Pearlman et al 1995a). The current study demonstrates that IL-12 significantly down-modulates the physiological and immunological changes in the lung that are induced by B. malayi larvae, including airway eosinophilia, deposition of eosinophil granule proteins and tracheal hyperreactivity.…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have demonstrated that reduced eosinophilia occurs when animals are given exogenous IL-12 during established Th-2 responses (Finkelman et al 1994, Wynn et al 1994, Pearlman et al 1995. However, when rIL-12 is given before a Th-2 response has been established, there is a more complete shift from Th-2 to Th-1 type responses.…”
Section: Discussionmentioning
confidence: 99%
“…Filters were dried and added to 5 ml scintillation fluid (EcoScint A; National Diagnostics, Inc., Manville, NJ), and the number of counts per minute was determined using a beta scintillation counter (Beckman Instruments, Fullerton, CA). Stimulation index was calculated as: cpm Ag stimulated/ cpm unstimulated (22).…”
mentioning
confidence: 99%
“…Measurements of IL-4, IL-5, and IFN-2* in culture supernarants were performed by two-site ELISA as described (22,25) using the following rnAbs: For IL-4, BVD6 was the coating and biotinylated BVD4 was the detecting mAb (obtained from Dr. F. Heinzel, Case Western Reserve University); for IL-5, TRFK5 was the trapping and TRFK4 was the detecting mAb (obtained from Dr. R. Coffman, DNAX, Palo Alto, CA); and for IFN-% R46A2 was the coating and XMG1.2 was the detecting mAb (obtained from American Type Culture Collection, Rockville, MD). Cytokines were measured after addition of streptavidinperoxidase and 0-phenylenediamine substrate (Sigma Chemical Co.), and absorbance was measured at 492 nm in a reader (Multiskan Plus MKII; Flow Laboratories, Inc., McLean, VA).…”
mentioning
confidence: 99%